2014
DOI: 10.1039/c4ra06475e
|View full text |Cite
|
Sign up to set email alerts
|

Dual drug loaded vitamin D3 nanoparticle to target drug resistance in cancer

Abstract: Overcoming drug resistance is one of the most challenging problems in cancer chemotherapy. Drug cocktails can overcome the drug resistance. However, multiple drug combinations lead to multifold increment of off-target toxicity, as well as the delivery of the required therapeutic amount of combined drugs remains problematic. To address these problems, we have developed a sub 200 nm vitamin D3 nanoparticle, which can contain a rational combination of dual drugs (PI103 and cisplatin or doxorubicin or proflavine).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…Furthermore, MALDI‐TOF experiments demonstrated the characteristic molecular ion peaks for free AZD6244 and cisplatin (Figure S15, S16 in the Supporting Information) to confirm their presence in active form after release from OA‐NPs in pH 5.5 at 24 h. From this drug release experiment, it was clear that OA‐NPs released the dual drugs in much higher quantity at pH 5.5 compared to pH 7.4 in a slow and sustained manner over 4 days. Previously, we have demonstrated that ester bonds between drug–lipid conjugates are more labile in acidic pH compared to physiological pH . Similarly, we anticipate that the ester linkage in oleic‐acid–AZD6244 conjugate ( 2 ) and Pt−O−CO− linkage in oleic‐acid–cisplatin conjugate ( 4 ) are more labile in acidic environment compared to neutral pH.…”
Section: Resultsmentioning
confidence: 71%
See 3 more Smart Citations
“…Furthermore, MALDI‐TOF experiments demonstrated the characteristic molecular ion peaks for free AZD6244 and cisplatin (Figure S15, S16 in the Supporting Information) to confirm their presence in active form after release from OA‐NPs in pH 5.5 at 24 h. From this drug release experiment, it was clear that OA‐NPs released the dual drugs in much higher quantity at pH 5.5 compared to pH 7.4 in a slow and sustained manner over 4 days. Previously, we have demonstrated that ester bonds between drug–lipid conjugates are more labile in acidic pH compared to physiological pH . Similarly, we anticipate that the ester linkage in oleic‐acid–AZD6244 conjugate ( 2 ) and Pt−O−CO− linkage in oleic‐acid–cisplatin conjugate ( 4 ) are more labile in acidic environment compared to neutral pH.…”
Section: Resultsmentioning
confidence: 71%
“…Cell viability : Cell viability assay of OA‐NPs using MTT reagents in HeLa, Hep3B, Hep3B‐R and MDA‐MB‐231 cells was performed by following the methods described in references and .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[18][19][20][21] Nanocarriers having size < 300 nm can accumulate specifically into the 4 tumor due to unique permeable tortuous angiogenic blood vessels. [22][23][24] Several nanocarriers including liposome, 25,26 polymeric nanoparticles, [27][28][29] dendrimers, 30,31 graphene oxide, 32,33 carbon-nanotubes, 34 mesoporous silica nanospheres, 35 nanocell, 36 gel-liposome, 37 layer-bylayer nanoparticle 38 and minicell 39 have been developed to co-deliver multiple drugs with combination with siRNA, DNA and therapeutic proteins. Despite having huge contribution of nanoplatforms in dual drug delivery in cancer therapeutics, not much attempts have been explored in delivering PI3K signaling inhibitors specifically into tumor to reduce their offtarget effects in healthy tissues as well as overcoming PI3K inhibitor related resistance.…”
Section: Introductionmentioning
confidence: 99%